Pembaharuan Kebijakan Formulasi Pelaksanaan Pidana Denda dan Pidana Tambahan Pembayaran Ganti Kerugian dalam Undang-Undang Perlidungan Data Pribadi - Idris Wasahua; Euis Nurul Bahriyah; Zulfikar Judge; Gousta Feriza (Jurnal Hukum Lex Generalis, 2025)
Law Number 27 of 2022 on Personal Data Protection regulates criminal sanctions in the form of fines and additional sanctions of compensation payment, enforced through the seizure of the convicted person’s assets or income. This policy aims to ensure the fulfillment of criminal sanctions and to provide legal protection for victims of personal data violations. However, this study finds that the current formulation policy contains fundamental weaknesses, as asset seizure may only be conducted after a court decision has obtained final and binding legal force, thereby allowing the convicted person to transfer assets during the lengthy criminal process. This research employs a normative legal research method using statutory and conceptual approaches. The findings indicate that such weaknesses may hinder the execution of fines and compensation payments and undermine the objectives of punishment. Therefore, this study recommends reformulating the policy by allowing asset seizure at the investigation stage as a legal guarantee to ensure effective enforcement of fines and compensation payments, as well as stronger protection for victims of personal data misuse.